Effects of incorporating retrieval into learning tasks: The complexity of the tasks matters. (June 2017) - Roelle, Julian; Berthold, Kirsten
Abstract: In an experiment with N = 192 university students, we examined whether the effects of incorporating retrieval into learning tasks depend on the learning tasks' complexity. The learning tasks consisted of adjunct questions that were provided together with expository texts relating to the domain of chemistry. We varied (a) whether the adjunct questions required the learners to summarize (low complexity) or generate inferences on the basis of provided information (high complexity) and (b) whether the adjunct questions were implemented in a closed-book style that required learners to engage in retrieval or in an open-book style that did not require learners to engage in retrieval while responding to the questions. Afterwards, all learners took either an immediate or a delayed criterion test. We found that the effect of incorporating retrieval depended on the complexity of the adjunct questions; the net benefit of incorporating retrieval was higher for the low complexity ones. Highlights: We varied whether adjunct questions were implemented in a closed- or open-book style. Furthermore, we varied the complexity of the adjunct questions. The effects of implementation style depended on the adjunct questions' complexity. The benefits of a closed-book implementation decreased as task complexity increased.